A breathable anti-allergic fabric and its preparation process

By using a three-layer composite structural fabric, combined with blended fibers, temperature-sensitive nanoparticle grafted modified polyester fibers and plant protein fibers, the problem of difficulty in taking into account both breathability and anti-allergicity of existing fabrics is solved, and high breathability and effective allergen barriers are achieved.

CN119369796BActive Publication Date: 2025-03-21VIOLET HOME TEXTILE TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411960942.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

It is difficult for existing fabrics to take into account both breathability and anti-allergicity. Breathable fabrics have poor durability and damaged breathability of anti-allergic fabrics.

Method used

A three-layer composite structural fabric is used, the base layer is blended grafted modified cotton fiber, natural bamboo fiber and modal fiber, the intermediate functional layer is temperature-sensitive nanoparticle grafted modified polyester fiber, and the surface layer is a fine mesh interwoven by plant protein fiber and polylactic fiber.

Benefits of technology

It achieves excellent breathability and efficient allergen barriers, providing a comfortable wearing experience and adapting to the physiological and environmental needs of the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369796B_ABST
    Figure CN119369796B_ABST
Patent Text Reader

Abstract

This invention provides a breathable and hypoallergenic fabric and its preparation process, belonging to the field of fabric preparation technology. The preparation process includes the following steps: preparation of thermosensitive nanoparticles; grafting thermosensitive nanoparticles onto modified polyester fibers; co-grafting polylysine and elastin onto modified blended fibers; and preparation of the breathable and hypoallergenic fabric. The fabric of this invention innovatively adopts a three-layer composite structure: the base layer is a blended grafted modified cotton fiber, natural bamboo fiber, and modal fiber, providing a solid foundation for breathability and skin-friendliness; the middle functional layer is thermosensitive nanoparticle grafted modified polyester fiber, with nano-silver antibacterial properties and sodium bismuthate photocatalytic decomposition of allergens without reducing the breathability of the polyester fiber; the surface layer is a fine mesh of plant protein fibers and polylactic acid fibers, which not only blocks the invasion of allergens but also ensures the free flow of moisture due to the fiber properties, thus guaranteeing excellent breathability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric preparation, and in particular to a breathable and anti-allergic fabric and a preparation process thereof. Background Art

[0002] With the continuous improvement of people's living standards and the enhancement of health awareness, the requirements for daily wear fabrics are no longer limited to basic aesthetics and durability. Breathability and anti-allergic properties are increasingly receiving the focus of consumers.

[0003] Although some fabric products on the current market claim to have breathable or anti-allergic properties, most of them cannot take into account the advantages of both at the same time, and lose one while gaining the other. As far as breathable fabrics are concerned, common cotton fabrics have certain breathability due to the hydrophilicity and porous structure of natural fibers, but cotton fabrics are prone to shrinkage and deformation, and their durability is poor; although chemical fiber fabrics are crisp and not easy to deform, they have poor breathability and are stuffy to wear. Fabrics that focus on anti-allergy are mostly made through post-finishing processes, such as coating the surface of the fabric with an anti-allergic coating to block allergens. However, this type of coating often blocks the original pores of the fabric, greatly weakening the breathability. After long-term wear, the coating will fall off, which will greatly reduce the anti-allergic effect.

[0004] Therefore, we proposed a breathable and anti-allergic fabric and its preparation process, which can not only ensure excellent breathability, keeping the skin dry and comfortable at all times, but also effectively block various allergens, giving people with allergies a safe wearing experience. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a breathable anti-allergic fabric and a preparation process thereof.

[0006] A preparation process of a breathable anti-allergic fabric comprises the following steps:

[0007] S1: Preparation of thermosensitive nanoparticles

[0008] Sodium bismuthate is used as the core, nanosilver is attached to the surface of the core, and then hexanoylated ethylene glycol chitosan is wrapped on the outermost side by dodecyl dimethyl benzyl ammonium chloride to form thermosensitive nanoparticles;

[0009] S2: Thermosensitive nanoparticles grafted modified polyester fibers

[0010] The polyester fiber is pretreated with an anhydrous ethanol solution of sodium hydroxide and KH-550, and then the pretreated polyester fiber is dispersed in a dispersion of thermosensitive nanoparticles, potassium persulfate is added, and the temperature is increased to react to obtain thermosensitive nanoparticle grafted modified polyester fiber;

[0011] S3: Polylysine and elastin co-grafted modified hybrid fiber

[0012] Cotton fiber, natural bamboo fiber and modal fiber are prepared into mixed fiber, and then the mixed fiber is oxidized to obtain oxidized mixed fiber, and polylysine and elastin are used to graft-modify the oxidized mixed fiber to obtain polylysine and elastin co-grafted modified mixed fiber;

[0013] S4: Preparation of breathable and anti-allergic fabrics

[0014] The grafted modified mixed fiber and the temperature-sensitive nanoparticle grafted modified polyester fiber are separately spun and woven into fabrics to obtain a base layer and an intermediate functional layer; the plant protein fiber and the polylactic acid fiber are woven into a fine mesh fabric to obtain a surface layer; the surface layer, the intermediate functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

[0015] Furthermore, step S1 of preparing the temperature-sensitive nanoparticles specifically comprises the following steps:

[0016] S1.1: Add 2-4 parts by weight of silver nitrate to 10-20 parts by weight of deionized water, place in an ice bath and stir for 10-20 minutes, then dropwise add 0.5-1 parts by weight of sodium borohydride solution, 2-3 seconds / drop, react for 20-30 minutes, to obtain a nanosilver solution;

[0017] S1.2: Dry 15-18 parts by weight of sodium bismuthate powder at 80-100°C for 2-4 hours, and then grind to a particle size of 80-100 nm, heat treat the dried and ground sodium bismuthate powder at 300-500°C for 2-4 hours in a nitrogen atmosphere, add the heat-treated sodium bismuthate powder to 50-60 parts by weight of ethanol, add 1-2 parts by weight of polyvinyl pyrrolidone, and then perform ultrasonic treatment for 20-30 hours, centrifuge the dispersion after ultrasonic treatment, and filter the supernatant after centrifugation through a 0.22 μm filter membrane to obtain a nano sodium bismuthate dispersion;

[0018] S1.3: Add 0.7-0.8 parts by weight of caprylated ethylene glycol chitosan to 70-80 parts by weight of deionized water, stir and dissolve for 10-20 minutes to obtain a caprylated ethylene glycol chitosan solution, add 10-12 parts by weight of the nanosilver solution to the nanosodium bismuthate dispersion, ultrasonically disperse the reaction mixture in the dark at room temperature and stir for 24-25 hours, then add 3-5 parts by weight of a dodecyldimethylbenzylammonium chloride aqueous solution, stir and mix for 20-30 minutes, then add the caprylated ethylene glycol chitosan solution, stir and mix for 24-25 hours, freeze-dry the mixture, wash it with anhydrous ethanol 2-3 times, and freeze-dry it again to obtain thermosensitive nanoparticles.

[0019] Furthermore, step S2 of grafting the thermosensitive nanoparticles onto the modified polyester fiber specifically comprises the following steps:

[0020] S2.1: 10-20 parts by weight of polyester fiber are placed in 100-200 parts by weight of a 5-15% sodium hydroxide solution, treated at 80-90°C for 30-45 minutes, then rinsed with a large amount of clean water until neutral, dried, and the dried polyester fiber is immersed in an anhydrous ethanol solution containing 150-180 parts by weight of 2-3% KH-550, stirred at room temperature for 2-3 hours, to obtain a pretreated polyester fiber;

[0021] S2.2: Disperse 3-5 parts by weight of thermosensitive nanoparticles in 30-40 parts by weight of phosphate buffer, ultrasonically disperse for 20-30 minutes to obtain a thermosensitive nanoparticle dispersion, disperse 3-5 parts by weight of pretreated polyester fibers in the thermosensitive nanoparticle dispersion, add 0.2-0.3 parts by weight of 0.05-0.1 mol / L potassium persulfate, heat to 70-80°C, stir and react for 3-5 hours under a nitrogen protective atmosphere, then filter and wash, and dry the washed fibers in an oven at 60-70°C to obtain thermosensitive nanoparticle grafted modified polyester fibers.

[0022] Furthermore, step S3 of co-grafting polylysine and elastin to modify the mixed fiber specifically comprises the following steps:

[0023] S3.1: 60-70 parts by weight of cotton fiber, 20-30 parts by weight of natural bamboo fiber and 10-20 parts by weight of modal fiber are placed in 200-300 parts by weight of 1wt% sodium dodecyl sulfate aqueous solution for ultrasonic cleaning for 1-2h, and then placed in 100-200 parts by weight of 95% ethanol solution for ultrasonic cleaning for 1-2h, and then washed with ultrapure water for 3-5 times, and dried in an oven at 70-80°C for 2-3 times to obtain clean cotton fiber, natural bamboo fiber and modal fiber;

[0024] S3.2: Clean cotton fiber, natural bamboo fiber and modal fiber are opened and mixed on an opener to form a mixed fiber, and then immersed in 200-300 parts by weight of 0.02-0.03 mol / L NaIO 4 The mixed fibers are mixed in an aqueous solution and stirred for 5-6 hours at 25-30° C. in the dark, then rinsed with deionized water 2-3 times, then immersed in 200-300 parts by weight of 0.01-0.02 mol / L ethylene glycol aqueous solution for 30-40 minutes, then rinsed with deionized water 2-3 times, and dried at 70-80° C. for 4-5 hours to obtain oxidized mixed fibers;

[0025] S3.3: Add 2-3 parts by weight of polylysine and 5-8 parts by weight of elastin to 100-120 parts by weight of deionized water, stir and mix for 20-30 minutes, then add 20-30 parts by weight of oxidized mixed fibers, stir and mix at 25-28°C for 1-2 hours, and finally wash with deionized water 2-3 times. Dry the washed mixed fibers at 37-38°C for 12-14 hours to obtain grafted modified mixed fibers.

[0026] Furthermore, step S4 of preparing the breathable anti-allergic fabric specifically includes the following steps:

[0027] S4.1: The grafted modified mixed fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain a base layer, and then the thermosensitive nanoparticle grafted modified polyester fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain an intermediate functional layer;

[0028] S4.2: The plant protein fiber and the polylactic acid fiber are mixed in a ratio of 6-7:3-4 and spun to make a blended yarn, the blended yarn is woven into a fine mesh fabric by a loom to obtain a surface layer, the surface layer, the middle functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

[0029] Furthermore, the concentration of the aqueous dodecyldimethylbenzylammonium chloride solution in step S1.3 is 0.1-0.2 mol / L.

[0030] A breathable anti-allergic fabric is prepared by any of the above-mentioned preparation processes for the breathable anti-allergic fabric.

[0031] Compared with the prior art, the present invention has at least the following beneficial effects:

[0032] 1. The fabric of the present invention innovatively adopts a three-layer composite structure: the base layer is a blended grafted modified cotton fiber, natural bamboo fiber and modal fiber. The unique micropores of bamboo fiber are matched with the soft texture of modal fiber, which lays a solid foundation for breathability and skin-friendliness. The bamboo fiber provides a certain support for the fabric, reduces deformation caused by external force, and can also alleviate shrinkage deformation. The middle functional layer is thermosensitive nanoparticle grafted modified polyester fiber. Nano silver is antibacterial and sodium bismuthate photocatalytically decomposes allergens without reducing the air permeability of polyester fiber. The surface plant protein fiber and polylactic acid fiber are interwoven into a fine network, which not only blocks the invasion of allergens, but also ensures the smooth flow of water vapor by relying on the fiber characteristics, thereby ensuring excellent breathability, keeping the skin dry and comfortable at all times, and can effectively block various allergens, giving allergic people a safe wearing experience.

[0033] 2. In the thermosensitive nanoparticles prepared by the present invention, the sodium bismuthate nanoparticles in the inner core have photocatalytic properties. Under daily lighting conditions, they can decompose allergens they come into contact with, such as pollen, dust mite fragments, mold spores and other organic macromolecular allergens, reducing the probability of them contacting the skin and causing allergic reactions. Nanosilver is coated on the surface of sodium bismuthate. Nanosilver can effectively kill various bacteria and fungi due to its excellent broad-spectrum antibacterial properties. Through the action of dodecyl dimethyl benzyl ammonium chloride, hexanoylated ethylene glycol chitosan is wrapped in the outermost layer to form an outer shell. The outer shell is hydrophilic and has a positive charge. Many allergen particles carry negative charges on their surface. Hexanodized ethylene glycol chitosan can capture allergens through electrostatic adsorption and firmly fix them on the surface of the shell. The anti-allergic effect can be achieved through the interaction of the three. In addition, as a natural polysaccharide derivative, hexanodized ethylene glycol chitosan has good biocompatibility and can gently "interact" with skin cells. When the skin contacts the fabric, hexanodized ethylene glycol chitosan can regulate the local immune microenvironment of the skin, inhibit the overactivation of immune cells, avoid the immune system's excessive allergic response to common weak allergens, and further enhance the anti-allergic effect.

[0034] 3. The temperature-sensitive nanoparticles prepared by the present invention are at the nanoscale. After being grafted on the surface of polyester fibers, they will not block the natural pores between fibers like traditional thick coatings or large particle additives. Polyester fibers originally have a certain air permeability. The attachment of nanoparticles only gives them an anti-allergic function, but does not interfere with the water vapor and air exchange channels of the fibers themselves, thereby ensuring the gas diffusion capacity of the fabric. When the human body generates heat during exercise and the body surface temperature rises, the energy obtained by the hexanoylated glycol chitosan molecules increases, and the weak interactions between and within the molecular chains, such as hydrogen bonds and van der Waals forces, will be broken. The molecular chains begin to stretch and extend, and change from a relatively curled and regular conformation to a more loose and disordered state. The nanoparticle structure stretches, and the gaps between fibers increase moderately, which accelerates heat dissipation and water vapor discharge, and improves air permeability efficiency. When the body temperature returns to normal and the ambient temperature decreases, the molecular kinetic energy decreases, the weak interactions that were previously destroyed gradually recover, and the particle structure shrinks. While maintaining the anti-allergic function, the fabric maintains moderate air permeability, dynamically adapts to the physiological and environmental needs of the human body, and makes the wearer feel comfortable all the time.

[0035] 4. The mixed fiber of the present invention is oxidized with sodium periodate to obtain an aldehyde-modified fiber surface. The polylysine and elastin can modify its surface through Schiff base reaction, so as to realize the co-grafting modification of polylysine and elastin into the mixed fiber. Elastin and polylysine are biocompatible. The polylysine molecule is positively charged and can attract the negatively charged groups on the skin surface, fit the skin contour, reduce the friction coefficient between the fabric and the skin, make the skin feel soft and smooth, like a second layer of skin, and greatly improve the wearing comfort. In addition, polylysine itself is a natural antibacterial agent and can play an antibacterial role. The grafted modified elastic Protein gives the fiber a certain elasticity, allowing the fiber to quickly return to its original shape after being stretched by external force. During the drying process, elastin will shrink and tighten the surrounding fibers, leaving tiny gaps between the fibers. Polylysine, with its smaller molecular structure, penetrates into the disordered areas inside the fiber and arranges the molecules in a regular manner. The two work together to optimize the fiber structure, leaving gaps between the fibers and forming a more regular, orderly and stable structure inside the fiber. The air conduction path in the fiber becomes more regular and smooth, thereby reducing the resistance to air flow and helping to improve air permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0037] Figure 1 The present invention is a flow chart of a process for preparing a breathable and anti-allergic fabric used in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following is a detailed description of the preparation process of a breathable anti-allergic fabric provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0039] Example 1

[0040] A preparation process of a breathable anti-allergic fabric, such as Figure 1 As shown, the following steps are included:

[0041] S1: Preparation of thermosensitive nanoparticles

[0042] S1.1: 2 parts by weight of silver nitrate was added to 10 parts by weight of deionized water, and the mixture was stirred in an ice bath for 10 minutes, and then 0.5 parts by weight of sodium borohydride solution was added dropwise at a rate of 2 seconds per drop, and the mixture was reacted for 20 minutes to obtain a nanosilver solution;

[0043] S1.2: Dry 15 parts by weight of sodium bismuthate powder at 80°C for 2 hours, then grind to a particle size of 80 nm, heat treat the dried and ground sodium bismuthate powder at 300°C for 2 hours in a nitrogen atmosphere, add the heat-treated sodium bismuthate powder to 50 parts by weight of ethanol, then add 1 part by weight of polyvinyl pyrrolidone, and then perform ultrasonic treatment for 20 hours, centrifuge the dispersion after ultrasonic treatment, and filter the supernatant after centrifugation through a 0.22 μm filter membrane to obtain a nano sodium bismuthate dispersion;

[0044] S1.3: Add 0.7 parts by weight of hexanoated ethylene glycol chitosan to 70 parts by weight of deionized water, stir and dissolve for 10 minutes to obtain a hexanoated ethylene glycol chitosan solution, add 10 parts by weight of the nanosilver solution to the nano-sodium bismuthate dispersion, ultrasonically disperse the reaction mixture at room temperature in the dark and stir for 24 hours, then add 3 parts by weight of a 0.1 mol / L dodecyl dimethyl benzyl ammonium chloride aqueous solution, stir and mix for 20 minutes, then add the hexanoated ethylene glycol chitosan solution, stir and mix for 24 hours, freeze-dry the mixture, wash it twice with anhydrous ethanol, and freeze-dry it again to obtain thermosensitive nanoparticles;

[0045] S2: Thermosensitive nanoparticles grafted modified polyester fibers

[0046] S2.1: 10 parts by weight of polyester fiber are placed in 100 parts by weight of 5% sodium hydroxide solution, treated at 80°C for 30 minutes, then rinsed with a large amount of clean water until neutral, dried, and the dried polyester fiber is immersed in an anhydrous ethanol solution containing 150 parts by weight of 2% KH-550, stirred at room temperature for 2 hours, to obtain pretreated polyester fiber;

[0047] S2.2: 3 parts by weight of the thermosensitive nanoparticles are dispersed in 30 parts by weight of phosphate buffer, and ultrasonically dispersed for 20 minutes to obtain a thermosensitive nanoparticle dispersion, 3 parts by weight of pretreated polyester fibers are dispersed in the thermosensitive nanoparticle dispersion, 0.2 parts by weight of 0.05 mol / L potassium persulfate are added, the temperature is raised to 70°C, and the reaction is stirred for 3 hours under a nitrogen protection atmosphere, and then filtered and washed, and the washed fibers are dried in an oven at 60°C to obtain thermosensitive nanoparticle grafted modified polyester fibers;

[0048] S3: Polylysine and elastin co-grafted modified hybrid fiber

[0049] S3.1: 60 parts by weight of cotton fiber, 20 parts by weight of natural bamboo fiber and 10 parts by weight of modal fiber are placed in 200 parts by weight of 1wt% sodium dodecyl sulfate aqueous solution for ultrasonic cleaning for 1 hour, and then placed in 100 parts by weight of 95% ethanol solution for ultrasonic cleaning for 1 hour each, and then washed with ultrapure water for 3 times, and dried in an oven at 70°C for 2 times to obtain clean cotton fiber, natural bamboo fiber and modal fiber;

[0050] S3.2: Clean cotton fiber, natural bamboo fiber and modal fiber are opened and mixed on an opener to form a mixed fiber, and then immersed in 200 parts by weight of 0.02 mol / L NaIO 4 The obtained fibers were mixed in an aqueous solution and stirred at 25°C in the dark for 5 h, then rinsed twice with deionized water, and then immersed in 200 parts by weight of a 0.01 mol / L ethylene glycol aqueous solution for 30 min, then rinsed twice with deionized water, and dried at 70°C for 4 h to obtain oxidized mixed fibers;

[0051] S3.3: 2 parts by weight of polylysine and 5 parts by weight of elastin are added to 100 parts by weight of deionized water, and the mixture is stirred for 20 minutes. Then, 20 parts by weight of the oxidized mixed fiber is added, and the mixture is stirred for 1 hour at 25°C. Finally, the mixed fiber is washed twice with deionized water, and the washed mixed fiber is dried at 37°C for 12 hours to obtain a grafted modified mixed fiber;

[0052] S4: Preparation of breathable and anti-allergic fabrics

[0053] S4.1: The grafted modified mixed fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain a base layer, and then the thermosensitive nanoparticle grafted modified polyester fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain an intermediate functional layer;

[0054] S4.2: The plant protein fiber and the polylactic acid fiber are mixed in a ratio of 6:3 and spun to make a blended yarn, the blended yarn is woven into a fine mesh fabric by a loom to obtain a surface layer, the surface layer, the middle functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

[0055] Example 2

[0056] A preparation process of a breathable anti-allergic fabric, such as Figure 1 As shown, the following steps are included:

[0057] S1: Preparation of thermosensitive nanoparticles

[0058] S1.1: 2 parts by weight of silver nitrate was added to 10 parts by weight of deionized water, and the mixture was stirred in an ice bath for 20 minutes, and then 0.5 parts by weight of sodium borohydride solution was added dropwise at a rate of 3 seconds per drop, and the mixture was reacted for 30 minutes to obtain a nanosilver solution;

[0059] S1.2: Dry 15 parts by weight of sodium bismuthate powder at 100°C for 4 hours, then grind to a particle size of 100 nm, heat treat the dried and ground sodium bismuthate powder at 500°C for 4 hours in a nitrogen atmosphere, add the heat-treated sodium bismuthate powder to 50 parts by weight of ethanol, then add 1 part by weight of polyvinyl pyrrolidone, and then perform ultrasonic treatment for 30 hours, centrifuge the dispersion after ultrasonic treatment, and filter the supernatant after centrifugation through a 0.22 μm filter membrane to obtain a nano sodium bismuthate dispersion;

[0060] S1.3: Add 0.7 parts by weight of caprylated ethylene glycol chitosan to 70 parts by weight of deionized water, stir and dissolve for 20 minutes to obtain a caprylated ethylene glycol chitosan solution, add 10 parts by weight of the nanosilver solution to the nano-sodium bismuthate dispersion, ultrasonically disperse the reaction mixture at room temperature in the dark and stir for 25 hours, then add 3 parts by weight of a 0.1 mol / L dodecyl dimethyl benzyl ammonium chloride aqueous solution, stir and mix for 30 minutes, then add the caprylated ethylene glycol chitosan solution, stir and mix for 25 hours, freeze-dry the mixture, wash it three times with anhydrous ethanol, and freeze-dry it again to obtain thermosensitive nanoparticles;

[0061] S2: Thermosensitive nanoparticles grafted modified polyester fibers

[0062] S2.1: 10 parts by weight of polyester fiber are placed in 100 parts by weight of 5% sodium hydroxide solution, treated at 90°C for 45 minutes, then rinsed with a large amount of clean water until neutral, dried, and the dried polyester fiber is immersed in an anhydrous ethanol solution containing 150 parts by weight of 2% KH-550, stirred at room temperature for 3 hours, to obtain the pretreated polyester fiber;

[0063] S2.2: 3 parts by weight of the thermosensitive nanoparticles are dispersed in 30 parts by weight of phosphate buffer, and ultrasonically dispersed for 30 minutes to obtain a thermosensitive nanoparticle dispersion, 3 parts by weight of pretreated polyester fibers are dispersed in the thermosensitive nanoparticle dispersion, 0.2 parts by weight of 0.05 mol / L potassium persulfate are added, the temperature is raised to 80°C, and the reaction is stirred for 5 hours under a nitrogen protection atmosphere, and then filtered and washed, and the washed fibers are dried in an oven at 70°C to obtain thermosensitive nanoparticle grafted modified polyester fibers;

[0064] S3: Polylysine and elastin co-grafted modified hybrid fiber

[0065] S3.1: 60 parts by weight of cotton fiber, 20 parts by weight of natural bamboo fiber and 10 parts by weight of modal fiber are placed in 200 parts by weight of 1wt% sodium dodecyl sulfate aqueous solution for ultrasonic cleaning for 2 hours, and then placed in 100 parts by weight of 95% ethanol solution for ultrasonic cleaning for 2 hours each, and then washed with ultrapure water for 5 times, and dried in an oven at 80°C for 3 times to obtain clean cotton fiber, natural bamboo fiber and modal fiber;

[0066] S3.2: Clean cotton fiber, natural bamboo fiber and modal fiber are opened and mixed on an opener to form a mixed fiber, and then immersed in 200 parts by weight of 0.02 mol / L NaIO 4 The obtained fibers were mixed in an aqueous solution and stirred at 30°C in the dark for 6 h, then rinsed with deionized water for 3 times, and then immersed in 200 parts by weight of a 0.01 mol / L ethylene glycol aqueous solution for 30 min, then rinsed with deionized water for 3 times, and dried at 80°C for 5 h to obtain oxidized mixed fibers.

[0067] S3.3: 2 parts by weight of polylysine and 5 parts by weight of elastin were added to 100 parts by weight of deionized water, and the mixture was stirred for 30 minutes. Then, 20 parts by weight of the oxidized mixed fiber was added, and the mixture was stirred for 2 hours at 28°C. Finally, the mixed fiber was washed with deionized water for 3 times, and the washed mixed fiber was dried at 38°C for 14 hours to obtain a grafted modified mixed fiber;

[0068] S4: Preparation of breathable and anti-allergic fabrics

[0069] S4.1: The grafted modified mixed fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain a base layer, and then the thermosensitive nanoparticle grafted modified polyester fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain an intermediate functional layer;

[0070] S4.2: The plant protein fiber and the polylactic acid fiber are mixed in a ratio of 6:3 and spun to make a blended yarn, the blended yarn is woven into a fine mesh fabric by a loom to obtain a surface layer, the surface layer, the middle functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

[0071] Example 3

[0072] A preparation process of a breathable anti-allergic fabric, such as Figure 1 As shown, the following steps are included:

[0073] S1: Preparation of thermosensitive nanoparticles

[0074] S1.1: Add 4 parts by weight of silver nitrate to 10-20 parts by weight of deionized water, place in an ice bath and stir for 10 minutes, then drop 1 part by weight of sodium borohydride solution at a rate of 3 seconds per drop and react for 20 minutes to obtain a nanosilver solution;

[0075] S1.2: Dry 18 parts by weight of sodium bismuthate powder at 80°C for 2 hours, then grind to a particle size of 80 nm, heat treat the dried and ground sodium bismuthate powder at 300°C for 2 hours in a nitrogen atmosphere, add the heat-treated sodium bismuthate powder to 60 parts by weight of ethanol, then add 2 parts by weight of polyvinyl pyrrolidone, and then perform ultrasonic treatment for 20 hours, centrifuge the dispersion after ultrasonic treatment, and filter the supernatant after centrifugation through a 0.22 μm filter membrane to obtain a nano sodium bismuthate dispersion;

[0076] S1.3: Add 0.8 parts by weight of caprylated ethylene glycol chitosan to 80 parts by weight of deionized water, stir and dissolve for 10 minutes to obtain a caprylated ethylene glycol chitosan solution, add 12 parts by weight of the nanosilver solution to the nano-sodium bismuthate dispersion, ultrasonically disperse the reaction mixture at room temperature in the dark and stir for 24 hours, then add 5 parts by weight of a 0.2 mol / L dodecyl dimethyl benzyl ammonium chloride aqueous solution, stir and mix for 20 minutes, then add the caprylated ethylene glycol chitosan solution, stir and mix for 24 hours, freeze-dry the mixture, wash it twice with anhydrous ethanol, and freeze-dry it again to obtain thermosensitive nanoparticles;

[0077] S2: Thermosensitive nanoparticles grafted modified polyester fibers

[0078] S2.1: 20 parts by weight of polyester fiber are placed in 200 parts by weight of 15% sodium hydroxide solution, treated at 80°C for 30 minutes, then rinsed with a large amount of clean water until neutral, dried, and the dried polyester fiber is immersed in an anhydrous ethanol solution containing 180 parts by weight of 3% KH-550, stirred at room temperature for 2 hours, to obtain pretreated polyester fiber;

[0079] S2.2: Disperse 5 parts by weight of the thermosensitive nanoparticles in 40 parts by weight of phosphate buffer, and ultrasonically disperse for 20 minutes to obtain a thermosensitive nanoparticle dispersion, disperse 5 parts by weight of the pretreated polyester fibers in the thermosensitive nanoparticle dispersion, add 0.3 parts by weight of 0.1 mol / L potassium persulfate, heat to 70°C, stir and react for 3 hours under a nitrogen atmosphere, then filter and wash, and dry the washed fibers in an oven at 60°C to obtain thermosensitive nanoparticle-grafted modified polyester fibers;

[0080] S3: Polylysine and elastin co-grafted modified hybrid fiber

[0081] S3.1: 70 parts by weight of cotton fiber, 30 parts by weight of natural bamboo fiber and 20 parts by weight of modal fiber are placed in 300 parts by weight of 1wt% sodium dodecyl sulfate aqueous solution for ultrasonic cleaning for 2 hours, and then placed in 200 parts by weight of 95% ethanol solution for ultrasonic cleaning for 1 hour each, and then washed with ultrapure water for 3 times, and dried in an oven at 70°C for 2 times to obtain clean cotton fiber, natural bamboo fiber and modal fiber;

[0082] S3.2: Clean cotton fiber, natural bamboo fiber and modal fiber were opened and mixed on an opener to form mixed fibers, and then immersed in 300 parts by weight of 0.03 mol / L NaIO 4 The obtained fibers were mixed in an aqueous solution and stirred at 25°C in the dark for 5 h, then rinsed with deionized water twice, and then immersed in 300 parts by weight of a 0.02 mol / L ethylene glycol aqueous solution for 30 min, and then rinsed with deionized water for 3 times, and dried at 70°C for 4 h to obtain oxidized mixed fibers.

[0083] S3.3: 3 parts by weight of polylysine and 8 parts by weight of elastin were added to 120 parts by weight of deionized water, and the mixture was stirred for 20 minutes. Then, 30 parts by weight of the oxidized mixed fiber was added, and the mixture was stirred for 1 hour at 25°C. Finally, the mixed fiber was washed twice with deionized water, and the washed mixed fiber was dried at 37°C for 12 hours to obtain a grafted modified mixed fiber;

[0084] S4: Preparation of breathable and anti-allergic fabrics

[0085] S4.1: The grafted modified mixed fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain a base layer, and then the thermosensitive nanoparticle grafted modified polyester fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain an intermediate functional layer;

[0086] S4.2: The plant protein fiber and the polylactic acid fiber are mixed in a ratio of 7:4 and spun to make a blended yarn, the blended yarn is woven into a fine mesh fabric by a loom to obtain a surface layer, the surface layer, the middle functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

[0087] Comparative Example 1

[0088] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes steps S1 and S2, replaces the thermosensitive nanoparticle grafted modified polyester fiber in step S4.1 with polyester fiber, and prepares a breathable and anti-allergic fabric without changing the other steps, which is recorded as Comparative Example 1.

[0089] Comparative Example 2

[0090] Compared with Example 1, the difference of Comparative Example 2 is that, in Comparative Example 2, the polylysine in step S3.3 is removed, and the other steps remain unchanged to prepare a breathable anti-allergic fabric, which is recorded as Comparative Example 2.

[0091] Comparative Example 3

[0092] Compared with Example 1, the difference of Comparative Example 3 is that, in Comparative Example 3, the elastin in step S3.3 is removed, and the other steps remain unchanged to prepare the breathable anti-allergic fabric, which is recorded as Comparative Example 3.

[0093] Comparative Example 4

[0094] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes the "adding 0.7 weight parts of caproylated ethylene glycol chitosan to 70 weight parts of deionized water, stirring and dissolving for 10 minutes to obtain a caproylated ethylene glycol chitosan solution" and "then adding 3 weight parts of 0.1 mol / L dodecyldimethylbenzyl ammonium chloride aqueous solution, stirring and mixing for 20 minutes, and then adding the caproylated ethylene glycol chitosan solution, stirring and mixing for 24 hours" in step S1.3, and the remaining steps remain unchanged to prepare a breathable anti-allergic fabric, which is recorded as Comparative Example 4.

[0095] The breathable anti-allergic fabrics of Examples 1-3, Comparative Example 1 and Comparative Example 4 were heated to 38°C to simulate the temperature of human body fever caused by strenuous exercise and increased body surface temperature. The air permeability of the breathable anti-allergic fabrics was tested using a fabric air permeability meter in accordance with GB / T543-1997 "Determination of Air Permeability of Fabrics". Three groups were tested and the results were averaged. The test results are shown in Table 1.

[0096] Table 1. Air permeability of Examples 1-3 and Comparative Example 1 heated to 38°C

[0097]

[0098] It can be seen from the data in Table 1 that when simulating the temperature of human body fever caused by intense exercise and increased body surface temperature, the air permeability of Comparative Example 1 and Comparative Example 4 decreased significantly, indicating that the prepared thermosensitive nanoparticles can accelerate heat dissipation and water vapor discharge, and improve air permeability efficiency. It can be seen from the data of Examples 1-3, Comparative Example 1 and Comparative Example 4 that the air permeability efficiency of the thermosensitive nanoparticles after being coated with hexanodized ethylene glycol chitosan is significantly improved compared with that before being coated.

[0099] The air permeability of the breathable anti-allergic fabrics of Examples 1-3 and Comparative Examples 2-3 was tested using a fabric air permeability meter in accordance with GB / T543-1997 "Determination of air permeability of fabrics". Three groups were tested and the results were averaged. The test results are shown in Table 2.

[0100] Table 2. Room temperature air permeability of Examples 1-3 and Comparative Examples 2-3

[0101]

[0102] It can be seen from the data in Table 2 that the data of Comparative Examples 2 and 3 are significantly lower than those of the embodiment, indicating that the use of polylysine and elastin co-grafted modified mixed fibers can significantly improve the air permeability of the fabric through their combined effect.

[0103] 40 mice were prepared, with 10 mice in each group. The hair on their backs was properly shaved to expose the back skin. The breathable anti-allergic fabrics prepared in Examples 1-3 and Comparative Examples 1 and 4 were respectively fixed on the skin on the backs of mice in each group to ensure that the fabrics were in close contact with the skin. A mixture of pollen, dust mite extracts, and mold spores was applied to the surface of the fabrics. After 48 hours, the reaction of the mouse skin was observed. If erythema, edema, itching, etc. appeared, it was an allergy. The test results are shown in Table 3.

[0104] Table 3. Antiallergic results of Examples 1-3 and Comparative Examples 1 and 4

[0105]

[0106] It can be seen from the data in Table 3 that the data of Comparative Example 1 is significantly higher than that of the embodiment, indicating that the thermosensitive nanoparticle grafted modified polyester fiber can achieve an anti-allergic effect. The data of Comparative Example 4 is lower than that of Comparative Example 1, but significantly higher than that of the embodiment, indicating that caproylation of ethylene glycol chitosan can have a certain anti-allergic effect and can synergize with nanosilver and sodium bismuthate to further enhance the anti-allergic effect.

[0107] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A preparation process of a breathable anti-allergic fabric, characterized in that: The steps include: S1: Preparation of thermosensitive nanoparticles Sodium bismuthate is used as the core, nanosilver is attached to the surface of the core, and then hexanoylated ethylene glycol chitosan is wrapped on the outermost side by dodecyl dimethyl benzyl ammonium chloride to form thermosensitive nanoparticles; S2: Thermosensitive nanoparticles grafted modified polyester fiber The polyester fiber is pretreated with an anhydrous ethanol solution of sodium hydroxide and KH-550, and then the pretreated polyester fiber is dispersed in a dispersion of thermosensitive nanoparticles, potassium persulfate is added, and the temperature is increased to react to obtain thermosensitive nanoparticle grafted modified polyester fiber; S3: Polylysine and elastin co-grafted modified hybrid fiber Cotton fiber, natural bamboo fiber and modal fiber are prepared into mixed fiber, and then the mixed fiber is oxidized to obtain oxidized mixed fiber, and polylysine and elastin are used to graft-modify the oxidized mixed fiber to obtain polylysine and elastin co-grafted modified mixed fiber; S4: Preparation of breathable and anti-allergic fabrics The grafted modified mixed fiber and the temperature-sensitive nanoparticle grafted modified polyester fiber are separately spun and woven into fabrics to obtain a base layer and an intermediate functional layer; the plant protein fiber and the polylactic acid fiber are woven into a fine mesh fabric to obtain a surface layer; the surface layer, the intermediate functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

2. The preparation process of a breathable anti-allergic fabric according to claim 1, characterized in that: Step S1: Preparation of temperature-sensitive nanoparticles, specifically comprising the following steps: S1.1: Add 2-4 parts by weight of silver nitrate to 10-20 parts by weight of deionized water, place in an ice bath and stir for 10-20 minutes, then dropwise add 0.5-1 parts by weight of sodium borohydride solution, 2-3 seconds / drop, react for 20-30 minutes, to obtain a nanosilver solution; S1.2: Dry 15-18 parts by weight of sodium bismuthate powder at 80-100°C for 2-4 hours, and then grind to a particle size of 80-100 nm, heat treat the dried and ground sodium bismuthate powder at 300-500°C for 2-4 hours in a nitrogen atmosphere, add the heat-treated sodium bismuthate powder to 50-60 parts by weight of ethanol, add 1-2 parts by weight of polyvinyl pyrrolidone, and then perform ultrasonic treatment for 20-30 hours, centrifuge the dispersion after ultrasonic treatment, and filter the supernatant after centrifugation through a 0.22 μm filter membrane to obtain a nano sodium bismuthate dispersion; S1.3: Add 0.7-0.8 parts by weight of caprylated ethylene glycol chitosan to 70-80 parts by weight of deionized water, stir and dissolve for 10-20 minutes to obtain a caprylated ethylene glycol chitosan solution, add 10-12 parts by weight of the nanosilver solution to the nanosodium bismuthate dispersion, ultrasonically disperse the reaction mixture in the dark at room temperature and stir for 24-25 hours, then add 3-5 parts by weight of a dodecyldimethylbenzylammonium chloride aqueous solution, stir and mix for 20-30 minutes, then add the caprylated ethylene glycol chitosan solution, stir and mix for 24-25 hours, freeze-dry the mixture, wash it with anhydrous ethanol 2-3 times, and freeze-dry it again to obtain thermosensitive nanoparticles.

3. The preparation process of a breathable anti-allergic fabric according to claim 2, characterized in that: Step S2: grafting and modifying polyester fibers with thermosensitive nanoparticles, specifically comprising the following steps: S2.1: 10-20 parts by weight of polyester fiber are placed in 100-200 parts by weight of a 5-15% sodium hydroxide solution, treated at 80-90°C for 30-45 minutes, then rinsed with clean water until neutral, dried, and the dried polyester fiber is immersed in an anhydrous ethanol solution containing 2-3% KH-550, stirred at room temperature for 2-3 hours, to obtain a pretreated polyester fiber; S2.2: Disperse 3-5 parts by weight of thermosensitive nanoparticles in 30-40 parts by weight of phosphate buffer, ultrasonically disperse for 20-30 minutes to obtain a thermosensitive nanoparticle dispersion, disperse 3-5 parts by weight of pretreated polyester fibers in the thermosensitive nanoparticle dispersion, add 0.2-0.3 parts by weight of 0.05-0.1 mol / L potassium persulfate, heat to 70-80°C, stir and react for 3-5 hours under a nitrogen protective atmosphere, then filter and wash, and dry the washed fibers in an oven at 60-70°C to obtain thermosensitive nanoparticle grafted modified polyester fibers.

4. The preparation process of a breathable anti-allergic fabric according to claim 3, characterized in that: Step S3: polylysine and elastin are co-grafted to modify the mixed fiber, which specifically includes the following steps: S3.1: 60-70 parts by weight of cotton fiber, 20-30 parts by weight of natural bamboo fiber and 10-20 parts by weight of modal fiber are placed in 200-300 parts by weight of 1wt% sodium dodecyl sulfate aqueous solution for ultrasonic cleaning for 1-2h, and then placed in 100-200 parts by weight of 95% ethanol solution for ultrasonic cleaning for 1-2h, and then washed with ultrapure water for 3-5 times, and dried in an oven at 70-80°C for 2-3 times to obtain clean cotton fiber, natural bamboo fiber and modal fiber; S3.2: Clean cotton fiber, natural bamboo fiber and modal fiber are opened and mixed on an opener to form mixed fibers, and then immersed in 200-300 parts by weight of 0.02-0.03 mol / L NaIO4 aqueous solution, and stirred and mixed for 5-6 hours at 25-30°C in the dark, and then rinsed with deionized water for 2-3 times, and then immersed in 200-300 parts by weight of 0.01-0.02 mol / L ethylene glycol aqueous solution for 30-40 minutes, and then rinsed with deionized water for 2-3 times, and dried at 70-80°C for 4-5 hours to obtain oxidized mixed fibers; S3.3: Add 2-3 parts by weight of polylysine and 5-8 parts by weight of elastin to 100-120 parts by weight of deionized water, stir and mix for 20-30 minutes, then add 20-30 parts by weight of oxidized mixed fibers, stir and mix at 25-28°C for 1-2 hours, and finally wash with deionized water 2-3 times. Dry the washed mixed fibers at 37-38°C for 12-14 hours to obtain grafted modified mixed fibers.

5. The preparation process of a breathable anti-allergic fabric according to claim 4, characterized in that: Step S4 is the preparation of breathable anti-allergic fabric, which specifically includes the following steps: S4.1: The grafted modified mixed fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain a base layer, and then the thermosensitive nanoparticle grafted modified polyester fiber is spun into yarn, and the yarn is treated and woven into fabric to obtain an intermediate functional layer; S4.2: The plant protein fiber and the polylactic acid fiber are mixed in a ratio of 6-7:3-4 and spun to make a blended yarn, the blended yarn is woven into a fine mesh fabric by a loom to obtain a surface layer, the surface layer, the middle functional layer and the base layer are connected by a knot to obtain a breathable and anti-allergic fabric.

6. The preparation process of a breathable anti-allergic fabric according to claim 2, characterized in that: The concentration of the aqueous dodecyldimethylbenzylammonium chloride solution in step S1.3 is 0.1-0.2 mol / L.

7. A breathable anti-allergic fabric, characterized in that: It is prepared by the preparation process of a breathable anti-allergic fabric as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Breathable fabric for manufacturing disposable masks and preparation method of breathable fabric

    CN111572124A

  • Antibacterial breathable knitted fabric and preparation method thereof

    CN118560124A